2018
DOI: 10.3758/s13421-018-0855-z
|View full text |Cite
|
Sign up to set email alerts
|

Learning new meanings for known words: Perturbation of original meanings and retention of new meanings

Abstract: Learning a new, unrelated meaning for a known word faces competition from the word's original meaning. Moreover, the connection of the word with its original meaning also shows a subtle form of interference, a perturbation, when tested immediately after learning. However, the long-term effects of both types of interference are unclear. The present study paired both high and low frequency words with new unrelated meanings, testing the fate of new and original meanings on three different days over one week as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 44 publications
3
25
1
Order By: Relevance
“…These could be reflected by the change of the N400 or LPC amplitudes on the probe word relative to the unlearned condition. According to the Suppression Hypothesis or Re-consolidation Hypothesis (Fang & Perfetti, 2019), we predicted the N400 amplitude of the URN (the unrelated new meaning learning) condition may be larger than that of the RN (the related new meaning learning) condition and the unlearned condition. The LPC amplitude of the URN condition may be smaller than the RN and the unlearned condition.…”
Section: The Current Studymentioning
confidence: 99%
See 2 more Smart Citations
“…These could be reflected by the change of the N400 or LPC amplitudes on the probe word relative to the unlearned condition. According to the Suppression Hypothesis or Re-consolidation Hypothesis (Fang & Perfetti, 2019), we predicted the N400 amplitude of the URN (the unrelated new meaning learning) condition may be larger than that of the RN (the related new meaning learning) condition and the unlearned condition. The LPC amplitude of the URN condition may be smaller than the RN and the unlearned condition.…”
Section: The Current Studymentioning
confidence: 99%
“…They suggest that the perturbation effect might result from a transient interaction of new and previously learned meanings during learning, involving a suppression of the original meaning so as to learn the new meaning. This could be reckoned as the Suppression Hypothesis (Fang & Perfetti, 2019).…”
Section: The Impact Of New Meaning Learning On the Previously Learned...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is important to note that the reminder only includes the words, not the definitions, which is the information that we evaluated on the final cued-recall test. Thirdly, although we consider the semantic judgment task used in Experiment 2 as a reliable marker of lexical integration based on previous studies (Bakker et al, 2015;Kaczer et al, 2018), it is also possible that participants can perform the task by accessing relevant episodic memories (Fang & Perfetti, 2019). Although the characteristics of the task, such as the short stimuli onset asynchrony, make it difficult to depend mostly on episodic retrieval, it is impossible to fully exclude its influence on the decision.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical context, for example, ambiguous emotional words could be used as an indirect measure to differentiate between populations, such as people with/without depression (Mogg et al, 2006) or people with/without dementia (Taler et al, 2009). Turning to the educational context, we note that ambiguity (e.g., Degani & Tokowicz, 2010;Fang & Perfetti, 2019) and emotionality (e.g., Altarriba & Basnight-Brown, 2011; Ferré, Ventura, Comesaña, & Fraga, 2015) are two variables that influence learning. For instance, Degani and Tokowicz (2010) found that ambiguous words are harder to learn than unambiguous words.…”
mentioning
confidence: 99%